Identifying A Learner’s Level of Foreign Language: Proficiency Tests and Underlying Cognitive Processes for Receptive Skills - Yaroslav Vladimirovich Golovko (Zien Journals, 2023)
One of the most frequently asked questions among foreign-language teachers of new groups of students deals with the ways to identify the level of target language proficiency of the learners. Modern resource databases propose numerous ready-made tests for that, which often causes the teachers to hesitate about the choice. This article aims to distribute receptive language skills of reading and listening across the proficiency levels of CEFR framework, thereby answering the ‘how’ question about the principles of comprehension and supplying necessary data for the further design or selection of proficiency tests.
Keywords: proficiency tests; receptive skills; CEFR; reading comprehension